SAT0585 Barriers To T2T Implementation: RA Patient's Perspectives about Comorbidities and Structural Damage in Therapeutic Decisions. (15th July 2016) - Laurindo, I.; Mota, L.; Romeiro, L.; Ranza, R.; Freitas, M.; Pereira, I.; Vasconcelos, J.; Brenol, C.; Rezende, L.; Bertolo, M.; Torigoe, D.
Abstract : Background: T2T strategies have been largely recognized and incorporated in national guidelines. Structural changes, functional impairment and comorbidities should be considered along with RA disease activity state when making therapeutic decisions. Objectives: To evaluate patient's perspectives on the interference of comorbidities and structural changes/functional impairment in treatment decisions. Methods: RA patients (1987 criteria) in regular follow-up were recruited from community (private practice) and academic public medical centers by 11 investigators in different urban and rural areas of the country. Structured questionnaires were applied and socio-demographics, disease activity and treatment data were collected. The focus of this study was two main questions: a) In your opinion, other diseases that you have can change the arthritis treatment? b) Do you think that having deformities modify your treatment? Affirmative answers would be followed by more specific questions. Statistical analysis: ANOVA or Kruskal-Wallis; Fisher or Fisher-Freeman-Halton (FFH) as needed; p<0.05. Data expressed as % [95%CI} or mean (SD). Results: 485 RA patients were included, 89.7% females, mean age 52.3 (13.8) years, 8.0 (5.2) years of education; 32.4% in use of biologics and 28.3% in private practice. Less than 40% of the patients considered that any of these conditions influenced the treatment. Deformities, surrogate for structural damage, were considered to imply in more severe disease or more pain and medications by respectively 54.8% and 34% of the positive responders (n=177); these patients were more frequently living in the northwest area (60.2vs 31.7%; =0.0001; [16.2–40]), were from higher socio-economic level (43.2vs30.2%; p=0.0001; [4, 1–21.7]), younger (49.4 (12.3) vs 54.3 (12, 7); p<0, 001) and with shorter disease duration (median 8.0 (range4.0–15) vs 12 (6.0–19); p<0.001). Regarding comorbidities, there were 39.4% (n=191) positive answers, predominantly from younger patients [51.3 (13.1) vs 54.5 (11.6); p<0.003]. The patients from private system (80.3 vs 56.3%;p=0.0004; [9.3–36.7]) and higher socio-economic level (71.8 vs55%; p=0.01;[2.9–30.1]), as well as patients with more schooling years (p<0.001) and shorter disease duration (p<0.041) worried that comorbidities could hinder the choice of arthritis medication, while some patients from public service (25.5vs9.8%;p=0, 01;[3.2–25.8]) and low socio-economic levels (14 vs 1.99%;p=0, 001;[4.1–20.6]) had concerns about too many pills. Conclusions: patient's skepticism about comorbidities or structural changes interfering with their therapeutic decisions is prevalent and needs to be addressed. Disclosure of Interest: None declared